Direct comparison of the abilities of bone marrow mesenchymal versus hematopoietic stem cells to reverse hyperglycemia in diabetic NOD.SCID mice. Issue 4 (4th July 2018) - Arany, Edith J.; Waseem, Muhammad; Strutt, Brenda J.; Chamson-Reig, Astrid; Bernardo, Adam; Eng, Elizabeth; Hill, David J.
ABSTRACT: Both bone marrow-derived hematopoietic stem cells (HSC) and mesenchymal stem cells (MSC) improve glycemic control in diabetic mice, but their kinetics and associated changes in pancreatic morphology have not been directly compared. Our goal was to examine the time course of improvements in glucose tolerance and associated changes in β-cell mass and proliferation following transplantation of equivalent numbers of HSC or MSC from the same bone marrow into diabetic non-obese diabetic severe combined immune deficiency (NOD.SCID) mice. We used transgenic mice with a targeted expression of yellow fluorescent protein (YFP) driven by the Vav1 gene promoter to genetically tag HSC and progeny. HSC were separated from bone marrow by fluorescence-activated cell sorting and MSC following cell culture. Equivalent numbers of isolated HSC or MSC were transplanted directly into the pancreas of NOD.SCID mice previously made diabetic with streptozotocin. Glucose tolerance, serum insulin, β-cell mass and β-cell proliferation were examined up to 28 days following transplant. Transplantation with MSC improved glucose tolerance within 7 days and serum insulin levels increased, but with no increase in β-cell mass. Mice transplanted with HSC showed improved glucose tolerance only after 3 weeks associated with increased β-cell proliferation and mass. We conclude that single injections of either MSC or HSC transiently improved glycemic control in diabetic NOD.SCID mice, but with different time courses. However, only HSC infiltrated the islets and were associated with an expanded β-cell mass. This suggests that MSC and HSC have differing mechanisms of action.